Talk by Suruhanjaya Syarikat Malaysia - Sorooshian, Shahryar; M., Waris; Senthil Kumar , T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (FIM-UMP, 2016)
With the support of FIM entrepreneurship program, a talk by Suruhanjaya Syarikat Malaysia (SSM) was held in UMP Gambang on 23 April 2016.